YX-112, a novel celastrol-derived PROTAC, inhibits the development of triple-negative breast cancer by targeting the degradation of multiple proteins - Gu, Yongxue; Yang, Mengmeng; Wang, Wenbin; Li, Lihua; Ma, Ying; Liu, Wenshan; Zhao, Qiang (Frontiers in Pharmacology, 2025)
BackgroundCelastrol is an effective component of the plant Tripterygium wilfordii Hook. f., which has a high inhibitory effect on triple-negative breast cancer. However, the therapeutic window of celastrol is narrow, and as a multi-target drug, its mechanism of action in triple-negative breast cancer is not very clear. Therefore, developing new celastrol derivatives has become an urgent task.MethodIn this work, we apply the PROTAC strategy to design and synthesis novel celastrol derivative. The antiproliferative activity of compound YX-112 against various types of cells was detected by CCK8 method. DIA-based quantitative proteomics, Western blot was used to explore the mechanism of compound YX-112 on triple-negative breast cancer MDA-MB-231 cells. Finally, the binding mode between compound YX-112 and target protein was predicted through molecular docking.ResultsWe developed a novel PROTAC YX-112 of celastrol, which was extremely sensitive to the triple-negative breast cancer MDA-MB-231 cells, with an IC50 value of 0.32 ± 0.04 μM, and its antiproliferative activity was 3 times that of celastrol. Subsequently, through DIA-based quantitative proteomics and Western blot validation experiments, it was found that YX-112 could target the degradation of CHEK1 and PIK3R2 proteins in MDA-MB-231 cells in a ubiquitin-proteasome dependent manner, indicating that it could be used as a degrader of CHEK1 and PIK3R2 proteins. Additionally, YX-112 could effectively inhibit the expression levels of CDK4 and p-AKT, and its inhibitory effect was stronger than that of celastrol. Finally, molecular docking predicted the binding mode between celastrol and CHEK1, showing that celastrol could form hydrogen bond interaction with the key residue GLN13.ConclusionThis study provides new insights into the derivation of celastrol and its molecular mechanisms of action.